Польща - Україна: економічні відносини в 90-х рр. - на початку ХХІ століть: особливості, проблеми, перспективи - Стрільчук, Людмила Василівна; Strilchuk, Liudmyla V. (Волинський державний університет імені Лесі Українки, 2007)
У статті на базі польських джерел охарактеризовано ставлення і розвиток, польсько-українських міждержавних економічних відносин у 90-х роках ХХ століття - на початку ХХІ століття. Розглянуто сучасні економічні проблеми прикордоння, європегіону і транскордонну співпрацю. Strilchuk L. V.

In the article on the basis of Polish sources the attitude and development of Polish-Ukrainian interstate economic relations in the 90 years of the XX century - the beginning of the XXI century was characterized. The contemporary economic problems of the border area, the europegion and cross-border cooperation are considered.
Poland - Ukraine: economic region in the period of 90-ies of the XX - the beginning of XX cent.: peculiarities, problems, perspectives.
Keywords: Польща; Україна; міждержавні стосунки; економічне співробітництво; європегіон; Poland; Ukraine; international relations; economic cooperation; Euroregion